Phenotypic differences in the appearance of soft rice and its endosperm structural basis - Fan, Peng; Xu, Jian; Wang, Zhijie; Liu, Guodong; Zhang, Zhenzhen; Tian, Jinyu; Wei, Haiyan; Zhang, Hongcheng (Frontiers in Plant Science, 2023)
In view of the significant differences among genotypes in the appearance of soft rice, it is necessary to conduct research on the differences in the appearance quality of soft rice and their mechanisms. It can provide a theoretical basis for the selection and breeding of superior appearance varieties at a later stage. In order to clarify the differences in appearance phenotypes between different soft rice genotypes and structural basis of endosperm structures behind the differences, four soft rice varieties were selected in this study, including two varieties with good-appearance and two varieties with cloudy appearance. The differences in appearance phenotypes and endosperm structure in mature grains of soft rice with different appearance phenotypes were scientifically analyzed. The development process of their endosperm differences at the filling stage was investigated. The results show that the difference in the rice appearance of soft rice varieties mainly lay in the chalk-free seed transparency and chalkiness. These differences were caused by two completely different types of endosperm structure. Fewer and smaller starch grain cavities were responsible for higher chalk-free transparency of soft rice grains, denser starch granules arrangement caused lower chalkiness of soft rice grains. Ten days after flowering, the starch granules in the back and heart of good-appearance soft rice were already significantly fuller and more closely packed than those of cloudy soft rice. At the same time, the number and area of starch granule holes were significantly smaller than those of cloudy soft rice. This difference gradually increased until maturity. Therefore, based on appearance evaluation, soft rice with good-appearance should have higher transparency and lower chalkiness. The endosperm starch granules should be full and tightly arranged. The number of starch grain cavities and the area should be smaller. These differences develop in the early stages of grouting and gradually increase.